MODEL KETERAMPILAN MEMBACA ANAK TUNARUNGU MELALUI MODIFIKASI PENDEKATAN KETERAMPILAN DASAR - SUPARNO, SUPARNO (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
Abstract The purpose of this action research was to increase the reading skill of the deaf children by modifying model of basic skill approach in the teaching-learning process. This study also aimed to explore the teaching-learning procedure of the reading skill of the deaf children for improving purposes. The population of this study was all students of the State Special School of the Deaf (SLB-B) in Yogyakarta. Tha cation research was conducted through the teaching-learning process of the reading skill in the classroom for 42 deaf children. The study was carried out in two cycles consisting of five learning sessions. The steps were reconnisance, planning, and combination of implementation and observation and finally reflection. The treatment was modifying the reading teaching –learning process, were conducted by the classroom teachers in collaboration with the researcher. Data were collected by administering the achievement test and analyzed by qualitative and quantitative methods. The results of this study show that (1) the action improved students reading skill, (2) modification model of basic skill approach is more effective in increasing reading skill of the deaf children than regular model,(3) this model is feasible for teaching the deaf children. Keywords: the deaf children, reading skill